Konsep Evaluasi Pembelajaran pada Keterampilan Membaca di Kelas Tinggi - Juni Sahla Nasution; Fadiah Adlina; Harits Heriadi; Shafa Azzahra Nurzal (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The ability to read is a basic skill that is very important in students' lives, both in academic contexts and in everyday life. Thus, evaluation of reading learning is very important in improving students' reading skills, supporting students' academic achievement, and providing a strong foundation for future learning. The method used in this research is literature review or literature review. The results of the research are: (1) Evaluation of reading learning in higher classes is an assessment process carried out by teachers to measure students' reading abilities at the upper secondary or secondary school level. (2) the types of learning evaluation are divided into 2, namely formative and summative evaluations, (3) the purpose of reading learning evaluation is to ensure that students develop the necessary reading skills and that reading teaching is effective.